An analysis of the cost-effectiveness of starting insulin detemir in insulin-naïve people with type 2 diabetes. (March 2015) - Home, Philip; Baik, Sei Hyun; Gálvez, Guillermo González; Malek, Rachid; Nikolajsen, Annie
Abstract Aims: There is limited evidence with respect to the cost-effectiveness of starting insulin in people with diabetes outside the 'western' world. The aim of this study was to assess the cost-effectiveness of starting basal insulin treatment with insulin detemir in people with type 2 diabetes (T2D) inadequately controlled on oral glucose-lowering drugs (OGLDs) in Mexico, South Korea, India, Indonesia, and Algeria. Methods: The IMS CORE Diabetes Model was used to project clinical and cost outcomes over a 30-year time horizon. Clinical outcomes, baseline characteristics and health state utility data were taken from the A1chieve study. A 1-year analysis was also conducted based on treatment costs and quality-of-life data. Incremental cost-effectiveness ratios (ICERs) were expressed as a fraction of GDP per capita, and WHO-CHOICE recommendations (ICER < 3.0) used to define cost-effectiveness. Results: Starting insulin detemir was associated with a projected increase in life expectancy (≥1 year) and was considered cost-effective in all of the studied populations with ICERs of −0.02 (Mexico), 0.00 (South Korea), 0.48 (India), 0.12 (Indonesia), and 0.88 (Algeria) GDP/quality-adjusted life-year. Cost-effectiveness was maintained after conducting sensitivity analyses in the 30-year and 1-year analyses. A projected increase in treatment costs was partially offset by a reduction in complications. The difference in overall costs between insulin detemir and OGLDs alone was USD518, 1431, 3510, 15, and 5219, respectively. Conclusion: Changes in clinical outcomes associated with starting insulin detemir in insulin-naïve individuals with T2D resulted in health gains that made the intervention cost-effective in five countries with distinct healthcare resources.